An Empirical Investigation of the Portuguese Housing Prices (2004-18) - Luo, Jianmin; Pereira, Renato; Dias, Ãlvaro (Journal of Reviews on Global Economics, 2020)
This article presents an integrated macro view of the Portuguese housing market with macroeconomic indicators. Firstly, it compares the housing market and several macroeconomic indicators from 2004 to 2018. Then, the dynamic analysis of the housing prices by different regions in Portugal and its typology included. Also, the article is complemented with the regression analysis to identify the relationship between the house prices and macroeconomic indicators. Results show that the current negative interest rates are increasing the demand for houses and the housing prices. The housing stock in Portugal is mostly fixed but may experience limited growth as the rebuild program and new constructions. GDP and the housing prices have a positive correlation. Houses in Algarve and Lisbon are markedly more expensive than in the interior. From the regression analysis, the unemployment rate is the closest correlated variable.